Pemanfaatan Pemasangan Bidai dengan Tingkat Nyeri pada Pasien di RSUD Kabupaten Karo: Utilization of Splinting with Pain Levels in Patients at Karo Regency Regional Hospital - Saragih, Hartaulina; Widyowati , Agustin; Ana Anggraini, Novita; Indasah , Indasah (Jurnal Abdi Keperawatan dan Kedokteran, 2024)
Nurses' work motivation is an important element that must be evaluated regularly, as motivation is a catalyst that drives individuals to move forward towards certain goals. High motivation in nurses can affect the quality of health services provided to patients. This study uses the SWOT analysis method to assess and prioritize strategies in increasing nurses' work motivation. Planned interventions include a morning monitoring and evaluation (monev) program for nursing documentation supervision consistent with standard regulations. Identification of nurses' work motivation and documentation supervision are carried out to find out the strengths, weaknesses, opportunities, and threats that exist. The results of the analysis show that the knowledge and skills of nurses regarding documentation techniques need to be improved through training and workshops. Optimizing nurses' work motivation can be done by periodic supervision and giving appreciation in the form of rewords. The implementation of the right strategy will improve the quality of nursing documentation and health services at Bobong Hospital.